(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This research focused on reading the poetry of the poet (Al-Kernag bint Haffan Al-Bakria), who was one of the poets of the pre-Islamic era. The researcher discussed her life, her personality, and her poetic themes, which were limited to the purpose of lamentation and satire. The study relied on the most important books of Arab heritage, which cited the poems of “Al-Kernnag” in various places. The study dealt with the psychological state of the poet through her lamentation for her husband and her people, and grief and regret for them. “Al-Kernag” is considered one of the feminist models that made a significant contribution to the movement of literature, thought, and criticism. The study was directed towards clarifying the features of the poetry of the pre-Islamic poet (Al-Kernag bint Haffan), and most of her poetic stations were characterized by the art of lamentation. The researcher tried to review the poems of “Al-Kernag”, examine the meanings of its various words, and clarify its various implications. The researcher dealt with an introduction, in which he reviewed the importance of looking at our Arab heritage and deducing its valuable meanings. The introduction dealt with a brief idea of the reasons for undertaking the research, the importance of the study, the objectives of the research, the methodology followed in the study, as well as the problem of the research and its limits. The research also dealt with a conclusion of the most important results reached by the researcher, this research was followed by references and sources.